Aromatase in human liver and its diseases. (30th April 2013) - Hata, Shuko; Miki, Yasuhiro; Saito, Ryoko; Ishida, Kazuyuki; Watanabe, Mika; Sasano, Hironobu
Abstract Estrogens play important roles in the cell proliferation and invasion of estrogen‐dependent human neoplasms. Aromatase overexpression has been also reported in hepatitis and hepatocellular carcinoma (HCC) compared with normal liver but its details in these hepatic disorders have remained unclear. Therefore, in this study, we first immunolocalized aromatase using immunohistochemistry in patients with liver cirrhosis, steatosis, hepatitis, HCC, and metastasis liver carcinoma (MLC) in order to study the detailed status of intrahepatic aromatase. Aromatase immunoreactivity was predominantly detected in nonneoplastic hepatocytes around tumor cells. We then evaluated the effects of an interaction between hepatocytes and carcinoma cells upon aromatase mRNA expression, using HepG2 as a substitute model of hepatocytes by coculture systems. Aromatase mRNA levels in HepG2 were significantly increased by coculture with all carcinoma cell lines examined. We also evaluated alternative splicing of aromatase exon 1 but the same splicing variant was used in HepG2 cells regardless of carcinoma cell lines employed in the coculture system. These findings obtained in HepG2 indicated that carcinoma cells, whether metastatic or primary, induced aromatase expression in adjacent normal hepatocytes possibly through the soluble aromatase inducible factors in human hepatic microenvironments.